Resistance of traditional storage traders in encounter mini-market competitors in Denpasar city - Kesuma, Made Ayunia; Setiawina, Nyoman Djinar (International research journal of management, IT and social sciences, 2019)
The results showed that the business location, working hours and a positive and significant effect on the income of traditional shop vendors in the city of Denpasar. The price of goods and distance has a negative and significant effect on the income of traditional traders in Denpasar City. Business capital and labor have a negative and insignificant effect on the income of traditional traders in Denpasar City. Business capital and income have a positive and significant effect on the resilience of traditional shop vendors in the city of Denpasar. Business location, distance, and working hours have an indirect effect on the resilience of traditional shop vendors through income. The price of goods and capital directly effect the resilience of traditional shop vendors in the city of Denpasar. The weakness of traditional shop vendors in the city of Denpasar from the arrangement and shape of the stalls is less neat and the lack of hospitality of traders, while the strength is that buyers can owe in the stalls. Opportunities for traditional traders in Denpasar can offer lower prices than Minimarkets.